PHYSICO-CHEMICAL ANALYSIS AND OPTIMIZATION OF ULTRASOUND ASSISTED EXTRACTION OF PHYTOCHEMICALS FROM KING’S RUBY GRAPES - M. Kaleem; A. Ahmad; T. Masud1and G. K. Raja (Journal of Animal and Plant Sciences, 2020)
King’s ruby is a seedless variety of grapes grown in the Phothohar region of Pakistan. In the present study, nutritional value of King’s ruby grapes was determined and extraction conditions were optimized using response surface central composite rotatable design of RSM using three variables at five levels. To get maximum yield of total phenolic content and total flavonoid content, the best combination of time of extraction, temperature of extraction and solvent concentration was determined. The process variable of time has the maximum effect on the functional components of extraction. The optimized condition for all the three parameters extract yield, total phenolic content and total flavonoid content was found to be 22.05 min time, 50.3 °C and 46.7 % ethanol concentration. The experimental result showed 4.84 mg/100g extract yield, 1.98 mg GAE/g phenolic content and 4.92 mg QEQ/g flavonoid content that is as per with predicted values. It is concluded that flavonoid content can be extracted efficiently using ultrasonic extraction that has a potential to be used as nutraceutical food ingredient. Ultrasonic extraction can efficiently extract bioactive components at low temperature and short period of time with maximum recovery.
Keywords: Ultrasound; Flavonoid; Response Surface; Optimization